Paradigm Shifts in Geographical Research and Geospatial Applications - Paul, Koyel; Jha, Vibhash Chandra (Sociedade & Natureza, 2021)
Geography enlightened a vast area of social sciences. It consists earth’s land and ocean surface, different landforms and their formation, evolution, sub-surface phenomena, atmosphere and related activities, environment and its attributes, environment as a habitat of living elements as well as a human being and their reciprocal relationships in a very critical and analytical approach.  From the inception of geography as a separate discipline, it evolved through its versatile, comprehensive and holistic nature. Alteration and modification change its nature through space and time. And accordingly, the established paradigm always changed depending on the demand of the geographers. This paper highlighted specifically the paradigm shift in geographical research with special reference to geospatial applications. Geography has two basic aspects,  Pure and  Applied. Recent trend shows that most of the geographical research is focused on the applied field rather than the pure aspects of the subject itself. The most interesting fact is that the applied research is basically depends upon the Geospatial technology. A distinct paradigm shifts have been taking place in both the Geographical Research and the Geospatial Technology through Digitalization.  The large growing population of the world require a logical and scientific shift in both pure and applied research in the domain of geography. Particular mention may be made in the fields of Geography such as geomorphology, population geography, urban geography, rural development and environmental geography. This paper also highlights the major paradigmn shifts in the behavioural geography, systematic geography, regional geography, medical geography, geospatial sustainability and cartography from paper map to digital map. It is now established  that no discipline can survive without adopting a new strategy and technology.